2020
DOI: 10.1111/jcpp.13347
|View full text |Cite
|
Sign up to set email alerts
|

Heightened sensitivity to the caregiving environment during adolescence: implications for recovery following early‐life adversity

Abstract: Background Adolescence has been proposed to be a period of heightened sensitivity to environmental influence. If true, adolescence may present a window of opportunity for recovery for children exposed to early‐life adversity. Recent evidence supports adolescent recalibration of stress response systems following early‐life adversity. However, it is unknown whether similar recovery occurs in other domains of functioning in adolescence. Methods We use data from the Bucharest Early Intervention Project – a randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…The simultaneous examination of the relations between resilience capacity, momentary stress, and affect with daily diurnal cortisol slopes remains underexplored. Further, resilience capacity should be most helpful in the presence of risk, which often is not captured in resilience studies 34 . Using retrospective reports of family risk as an index of prior adversity, our study recruited participants from three groups: (1) Resilient, including individuals who originated from risky families and reported high current resilience capacity, (2) Vulnerable, including individuals from risky families but with low reported current resilience capacity, and (3) Control, including individuals with low early family risk and average current symptoms of anxiety and depression.…”
Section: Aims and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The simultaneous examination of the relations between resilience capacity, momentary stress, and affect with daily diurnal cortisol slopes remains underexplored. Further, resilience capacity should be most helpful in the presence of risk, which often is not captured in resilience studies 34 . Using retrospective reports of family risk as an index of prior adversity, our study recruited participants from three groups: (1) Resilient, including individuals who originated from risky families and reported high current resilience capacity, (2) Vulnerable, including individuals from risky families but with low reported current resilience capacity, and (3) Control, including individuals with low early family risk and average current symptoms of anxiety and depression.…”
Section: Aims and Hypothesesmentioning
confidence: 99%
“…Given that the definition of resilience necessitates the presence of adversity, we measured the resilience of our participants against a context of early family life risk and current transitory stress by studying emerging adults at a developmental transition who moved at least interstate often internationally for tertiary studies. Most studies measure resilience based on self-report without the reporting of risks 34 . We also categorized participants from low-risk families into the Control group as demographically similar comparisons.…”
Section: Limitation and Strengthsmentioning
confidence: 99%
“…Critically, some recent evidence—in addition to that highlighted earlier (e.g., Andersen et al, in press)—indicates that this is indeed the case even when early-life adversity is severe. Especially, notable is Colich et al’s (2021) work investigating the adolescent experiences and development of children raised in extremely deprived Romanian orphanages prior to placement in foster care. Results revealed that the higher the quality of caregiving at this later developmental period, the greater the individual’s reward responsivity and the lower the levels of internalizing and externalizing symptoms.…”
Section: Early Adversity and Later Plasticitymentioning
confidence: 99%
“…The relations between resilience capacity, momentary stress, and affect with daily diurnal cortisol slopes remains underexplored. Further, resilience capacity should be most helpful in the presence of risk, which often is not captured in resilience studies (Colich et al, 2020). Using retrospective reports of family risk as an index of prior adversity, our study recruited participants from three groups: (1) Resilient, including individuals who originated from risky families and reported high current resilience capacity, (2) Vulnerable, including individuals from risky families but with low reported current resilience capacity, and (3) Control, including individuals with low early family risk and average current symptoms of anxiety and depression.…”
Section: Aims and Hypothesesmentioning
confidence: 99%
“…Given that the de nition of resilience necessitates the presence of adversity, we measured the resilience of our participants against a context of early family life risk and current transitory stress by studying emerging adults at a developmental transition who moved at least interstate often internationally for tertiary studies. Most studies measure resilience based on selfreport without the reporting of risks (Colich et al, 2020). We also categorized participants from low-risk families into the Control group as demographically similar comparisons.…”
Section: Limitation and Strengthsmentioning
confidence: 99%